Implementasi Interprofessional Education (IPE) dalam Kurikulum Pendidikan Kebidanan: Literature Review - Ashifa, Ade Nurul; Susanti, Ari Indra; Susiarno, Hadi (Universitas Gadjah Mada, 2025)
Background: The increasing complexity of maternal and child health services in the era of globalization demands effective collaboration among healthcare professionals. Interprofessional Education (IPE) is recognized as a strategic approach to enhance teamwork and communication skills among midwifery students. However, the effective forms and methods of IPE implementation in midwifery education remain underexplored, especially in Indonesia.Methods: This literature review aimed to identify various forms and methods of IPE implementation in midwifery education to improve interprofessional collaboration. Articles were selected from databases such as Google Scholar, Scopus, and Sage Journals, focusing on studies published between 2017 and 2024. The review included qualitative, quantitative, and mixed-method studies that discussed IPE implementation and its impact on collaborative skills. The PRISMA flow diagram was used to document the selection process.Results: Twelve articles from diverse countries were reviewed, revealing four main forms of IPE implementation: interprofessional simulation and workshops, portfolio/reflection-based learning and assessment, structured programs and certification, and collaborative clinical experiences. These approaches were shown to improve students’ communication, teamwork, and understanding of professional roles. Institutional support and resource investment were identified as key factors for successful IPE integration.Conclusion: IPE implementation in midwifery education enhances students’ interprofessional collaboration skills and has the potential to improve the quality of maternal and child health services. Comprehensive curriculum design and institutional commitment are essential to maximize the benefits of IPE in preparing future midwives for collaborative practice.